(untitled) (Revista de Estudos da Linguagem, 2025)
Oral deaf people (i.e., people with hearing loss who have learned an oral language) are typically less exposed to auditory and linguistic input than normal hearing peers and might struggle with figurative language comprehension. Our aim is to investigate primary metaphor and idiom comprehension by oral deaf who use hearing amplification devices or cochlear implants. To this end, we used a verbal primary metaphor task, a non-verbal primary metaphor task and an idiom comprehension task. One hundred fifty-one participants took part in the study (57 oral deaf and 97 normal hearing individuals, subdivided into three age levels). Results show that comprehension follows an improvement pattern as participants’ age increases in both experimental and control groups. For the oral deaf individuals, a delay was found for all verbal tasks. For the non-verbal metaphor task, only kids differed statistically, with the oral deaf children performing worse than their counterparts. In conclusion, figurative language comprehension can be more challenging for oral deaf individuals when presented verbally than non-verbally, particularly from adolescence onwards, in comparison to normal hearing peers. This study contributes to informing clinicians and educators about comprehension of primary metaphors and idioms in oral deaf individuals, which may help to identify language impairments and create interventions for figurative language comprehension.